The process of animal domestication - Sánchez-Villagra, Marcelo R. (Princeton University Press, 2022)
"The first modern scholarly synthesis of animal domestication Across the globe and at different times in the past millennia, the evolutionary history of domesticated animals has been greatly affected by the myriad, complex, and diverse interactions humans have had with the animals closest to them. The Process of Animal Domestication presents a broad synthesis of this subject, from the rich biology behind the initial stages of domestication to how the creation of breeds reflects cultural and societal transformations that have impacted the biosphere.Marcelo Sánchez-Villagra draws from a wide range of fields, including evolutionary biology, zooarchaeology, ethnology, genetics, developmental biology, and evolutionary morphology to provide a fresh perspective to this classic topic. Relying on various conceptual and technical tools, he examines the natural history of phenotypes and their developmental origins. He presents case studies involving mammals, birds, fish, and insect species, and he highlights the importance of domestication for the comprehension of evolution, anatomy, ontogeny, and dozens of fundamental biological processes.Bringing together the most current developments, The Process of Animal Domestication will interest a wide range of readers, from evolutionary biologists, developmental biologists, and geneticists to anthropologists and archaeologists"--